2016
DOI: 10.1248/cpb.c16-00224
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Orally Disintegrating Tablets Containing Powdered Tea Leaves with Enriched Levels of Bioactive Compounds by Means of Microwave Irradiation Technique

Abstract: In the present study, a microwave treatment process has been applied to prepare orally disintegrating tablets (ODTs) containing powdered tea leaves with enriched levels of the anti-inflammatory compounds such as chafuroside A (CFA) and chafuroside B (CFB). The use of distilled water as the adsorbed and granulation solvents in this preparation process afforded tablets with a long disintegration time (more than 120 s). The CFA and CFB contents of these tablets did not also change after 4 min of microwave irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…All formulations had hardness values of over 13 N (Fig. 2B), which is sufficient hardness for a 5-mm diameter tablet (Tanaka et al, 2016). This is because the excipient d -mannitol melts at 168 °C and forms strong particle-to-particle bonds during microwave irradiation.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…All formulations had hardness values of over 13 N (Fig. 2B), which is sufficient hardness for a 5-mm diameter tablet (Tanaka et al, 2016). This is because the excipient d -mannitol melts at 168 °C and forms strong particle-to-particle bonds during microwave irradiation.…”
Section: Resultsmentioning
confidence: 95%
“…ODTTs were prepared using an established method with a slight modification (Tanaka et al, 2016). Oolong tea leaves were ground using a standard tea grinder (Teafine Mutow, Shizuoka, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the disintegration time of these tablets was considerably improved (less than 20 s) compared with the microwave-untreated tablets, and there were 7- and 11-fold increases in their CFA and CFB contents. Hardness and friability characteristics of the microwave treated tablets were found to be acceptable [ 23 ]. Lamotrigine ODTs were formulated using microwave-assisted development of ODTs based on simple direct compression tableting technology.…”
Section: Preparation Of Odts For Immediate Release Applicationsmentioning
confidence: 99%
“…Formulations of chafurosides have been designed to extend their therapeutic applications. Orally disintegrating tablets containing powdered tea leaves have been developed using a microwave treatment method, 10) which increases the contents of chafurosides A and B by promoting their formation from precursor molecules while retaining immediate disintegration properties and tablet hardness. 11) A self-assembled micellar formulation of chafuroside A with improved solubility and, as a result, enhanced antiinflammatory activity, was reported.…”
Section: Introductionmentioning
confidence: 99%